EFFECT OF ECONOMIC HARDSHIP ON ENTREPRENEURIAL STRESS AMONG YOUTH IN RIVERS STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Entrepreneurs have made significant contributions to the development and growth of many countries and have become an integral part of the ecosystem through which businesses operate. Many believe it is the primary driver of socioeconomic development and wealth creation and positively contributes to generating employment opportunities. On the other hand, there are indications that the growing economic downturns have been unfavorable to business owners and entrepreneurs. Therefore, the purpose of this paper was to investigate economic turmoil as a potential factor that could explain the variation in the amount of stress experienced by entrepreneurs. The research was carried out with the participation of a convenience sample consisting of two hundred and thirteen business owners or entrepreneurs from various business hubs located in the Port Harcourt Metropolis, Rivers State, Nigeria. To test the hypothesis, a simple regression analysis was conducted, which revealed that economic hardship was a statistically significant predictor of entrepreneurial stress. The obtained F (1,211) value was 32.61, and the p-value was less than 0.000. Thus, the result supported the hypothesis that economic difficulties would significantly predict the stress experienced by entrepreneurs. Furthermore, the R2 indicated that the impact of economic difficulties accounted for approximately 46.3% of the total variance in the stress experienced by entrepreneurs. This paper concluded that economic hardship is among the most critical contributors to entrepreneurial stress.